(untitled) (Kathmandu University Medical Journal, 2014)
Background Pelvic organ prolapse is a multidimensional phenomenon. The manifestations of renal involvement following pelvic organ prolapse ranges from acute to chronic renal failure and may also lead to end stage renal failure. Prolonged duration and its severity in pelvic organ prolapse are responsible for renal impairment. Objectives This study will find out the incidence of renal impairment among women with pelvic organ prolapse undergoing surgical management. It will also help to establish the association of renal impairment with degree and duration of pelvic organ prolapse. Methods This prospective study includes cases of pelvic organ prolapse who underwent surgical management from the year 2009-2012 in Dhulikhel hospital. Total 140 cases were assessed with age, duration and different symptoms. Clinical examination was done to find out the degree of prolapse and graded according to Baden Walker classification. Urine routine and microscopic examination, renal function test and abdominopelvic sonography were performed routinely. Renal impairment was assessed using hydronephrosis and creatinine clearance. Creatinine clearance was calculated using patient’s weight and serum creatinine value by Cockcroft and Gault formula. Results Among 140 cases, 8 (5.7%) patients had procedentia, 106 (75.7%) had third degree, 22 (15.7%) had second degree, and four (2.8%) patients had first degree uterine prolapse. The mean duration of prolapse was found to be 11.47 years. Total 5 (3.57%) patients had hydronephrosis. Four had moderate and one had severe hydronephrosis. Total 49 (34.1%) patients had moderate to severe renal failure. Forty six (32%) in stage III moderate reduction in creatinine clearance, 2 (1.4%) with severe reduction and 1(0.7%) in end stage renal failure. Conclusion Renal impairment is a common entity among women with pelvic organ prolapse. Both hydronephrosis and degree renal impairment correlates correspondingly with the duration and severity of prolapse. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11031 Kathmandu University Medical Journal Vol.11(1) 2013: 71-74